40th Anniversary of the Brazilian Journal of Biometrics - Rodrigues, Paulo Canas; Fernandes, Tales Jesus; Scalon, João Domingos; Malheiros, Euclides Braga (My University, 2022)
2022 marks the 40th anniversary of the Brazilian Journal of Biometrics. In honor of this occasion, the last issue of 2022 features invited contributions from our editorial board, along with a brief journal history.
Keywords: Biometrics; Brazilian Journal of Biometrics; Data science; Statistics